Increasing the Growth and Yield of Green Bean Plants (Vigna radiata L.) by Providing Fly Ash and Organic Materials in Ultisol Soil - Nursiani Lubis; Idwar; Fetmi Silvina; Via Permata Sari; Faizul Luthfi (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Mung bean (Vigna radiata L.) is an important source of plant-based protein; however, its production has been declining. Efforts to increase mung bean production can be achieved through land extensification and intensification. Extensification can be implemented by utilizing Ultisol soils, while intensification can be accomplished through the application of fly ash and organic amendments. This study aimed to evaluate the effects of fly ash and organic amendments on the growth and yield of mung bean (Vigna radiata L.) grown on Ultisol soil. The experiment was conducted at the experimental field and Soil Laboratory of the Faculty of Agriculture, Riau University, using three fly ash rates and four organic amendments. Data were statistically analyzed using analysis of variance (ANOVA), followed by Duncan's New Multiple Range Test (DNMRT) at the 5% significance level, using SAS software. Observed parameters included the number of filled pods, percentage of filled pods, dry seed weight per plant, root volume, and percentage of effective root nodules. The results showed that fly ash application increased soil pH and organic carbon content while reducing exchangeable aluminum (Al-dd). The application of cattle manure at different fly ash rates significantly increased the number and percentage of filled pods, dry seed weight per plant, root volume, and the percentage of effective root nodules. Fly ash application at rates of 12.5 and 25 g per polybag did not result in significant differences in the number of filled pods, percentage of filled pods, dry seed weight per plant, or root volume compared to the control, but it did significantly increase the percentage of effective root nodules. Overall, applying 25 g of cattle manure per polybag resulted in higher mung bean growth and yield on Ultisol soil than cattle urine or cattle manure bokashi across various fly ash rates.